(untitled) (Scientific journal of the Fergana State University, 2024)
The role and development of foreign languages are multifaceted and are influenced by historical, cultural, economic, and educational factors. The study and dissemination of foreign languages play a crucial role in global communication, intercultural understanding, diplomacy, international trade, and academic research. This article reviews the taxonomy and innovative methods used in current language teaching practice.